Risk perception of smokers on graphic warning labels: a qualitative study in East Nusa Tenggara, Indonesia - Enjelita Mariance Ndoen; Helga Jillvera Nathalia Ndun (Intelektual Pustaka Media Utama, 2022)
The Indonesian government has mandated Graphic warning labels (GWLs) on cigarette packages to achieve more comprehensive tobacco control interventions. However, smoking prevalence remains a public health issue in Indonesia. This current qualitative research aimed to explore the effect of cigarette GWLs on smokers’ perceptions about smoking and cigarette packaging in East Nusa Tenggara (NTT) and its influence on smoking behavior. The study participants consisted of 15 current smokers who were individually interviewed by using a semi-structured interview guide. Data were analyzed using a thematic analysis technique. Most participants perceived smoking as health-risk behavior yet lowered their risk perceptions of smoking-related diseases due to positive feelings of perceived current benefits of smoking and personal justification for smoking. None expressed any intention to quit or showed smoking behavior changes due to GWLs exposure on cigarette packages. Participants also implicitly expressed themselves as victims willing to quit but unable and unconfident to act due to smoking addiction and other stressors. In contrast, others perceived themselves as risk-taker who enjoyed smoking. Further research is still needed to provide robust evidence on GWLs effectiveness on smoking perception and smokers’ cognitive and behavioral responses. Behavior change interventions should address positive feelings experienced and rationalization made by smokers to provide effective risk communication.